2014
DOI: 10.1177/0361684314560730
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Discrimination and Mental Health Disparities Faced By Black Sexual Minority Women Using a Minority Stress Framework

Abstract: Black sexual minority women are triply marginalized due to their race, gender, and sexual orientation. We compared three dimensions of discrimination—frequency (regularity of occurrences), scope (number of types of discriminatory acts experienced), and number of bases (number of social statuses to which discrimination was attributed)—and self-reported mental health (depressive symptoms, psychological well-being, and social well-being) between 64 Black sexual minority women and each of two groups sharing two of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
117
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(130 citation statements)
references
References 80 publications
(149 reference statements)
9
117
0
3
Order By: Relevance
“…It may be that these women make distinctions between sources of discrimination and do not experience their racial minority status as contributing to discrimination due to their sexual orientation. Consistent with this finding, Calabrese et al (2015) found that Black and White lesbian women did not significantly differ in reported sexual minority discrimination. On the other hand, our single item discrimination measure may have limited our ability to capture variability in perceived discrimination, thus attenuating the association between race and sexual minority discrimination.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…It may be that these women make distinctions between sources of discrimination and do not experience their racial minority status as contributing to discrimination due to their sexual orientation. Consistent with this finding, Calabrese et al (2015) found that Black and White lesbian women did not significantly differ in reported sexual minority discrimination. On the other hand, our single item discrimination measure may have limited our ability to capture variability in perceived discrimination, thus attenuating the association between race and sexual minority discrimination.…”
Section: Discussionsupporting
confidence: 64%
“…In fact, in a recent meta-analysis, minority statuses of race, sex, and sexual orientation were each associated with poorer psychological well-being. Also, Black sexual minority women compared to White sexual minority women, reported more discrimination, which was then associated with poorer well-being (Calabrese, Meyer, Overstreet, Hale, & Hansen, 2015). Also, Black lesbian, gay, bisexual and transgender (LGBT) individuals may experience more psychological distress and emotional disorders (Balsam, Molina, Beadnell, Simoni, & Walters, 2011; King et al, 2008; O'Donnell, Meyer, & Schwartz, 2011) than White LGBT individuals.…”
Section: Race Ses and Minority Stressmentioning
confidence: 99%
“…Over the years, the MSM has received substantial empirical support, particularly when predicting sexual orientation-related disparities in mental health morbidity (Cochran, 2001; Cochran & Mays, 2009; Eldahan et al, 2016; Feinstein et al, 2012; Hatzenbuehler, 2009; Lehavot & Simoni, 2011; McCabe, Bostwick, Hughes, West, & Boyd, 2010; Meyer, 2003; Meyer, Schwartz, & Frost, 2008; Pachankis, Rendina, et al, 2015; Ueno, 2010). However, the MSM is less robust at explaining frequently observed patterns of gender (Cochran, Bandiera, & Mays, 2013; Cochran & Mays, 2013) or racial/ethnic (Bostwick, Boyd, Hughes, West, & McCabe, 2014; Bostwick, Meyer, et al, 2014; Calabrese, Meyer, Overstreet, Haile, & Hansen, 2015) differences within the LGB population. For example, although the MSM predicts that the double marginalization of sexual and racial/ethnic minority status should result in greater mental health disparities among LGB persons of color, current evidence is not fully supportive of this prediction (Bostwick, Meyer, et al, 2014; Calabrese et al, 2015; Cochran, Mays, Alegria, Ortega, & Takeuchi, 2007).…”
mentioning
confidence: 99%
“…However, the MSM is less robust at explaining frequently observed patterns of gender (Cochran, Bandiera, & Mays, 2013; Cochran & Mays, 2013) or racial/ethnic (Bostwick, Boyd, Hughes, West, & McCabe, 2014; Bostwick, Meyer, et al, 2014; Calabrese, Meyer, Overstreet, Haile, & Hansen, 2015) differences within the LGB population. For example, although the MSM predicts that the double marginalization of sexual and racial/ethnic minority status should result in greater mental health disparities among LGB persons of color, current evidence is not fully supportive of this prediction (Bostwick, Meyer, et al, 2014; Calabrese et al, 2015; Cochran, Mays, Alegria, Ortega, & Takeuchi, 2007). …”
mentioning
confidence: 99%
“…Stigma negatively affects the health and well-being of socially marginalized groups (Calabrese, Meyer, Overstreet, Haile, & Hansen, 2015; Cook, Juster, Calebs, Heinze, & Miller, 2017; Hatzenbuehler & McLaughlin, 2014; Hatzenbuehler, Phelan, & Link, 2013; Rendina et al, 2017). Researchers have quantified the stigmatization of marginalized groups by administering validated surveys to assess the prevalence of negative attitudes toward members of socially stigmatized groups (Helms & Waters, 2016; Herek, 2002).…”
Section: Introductionmentioning
confidence: 99%